2004
DOI: 10.1111/j.1601-183x.2004.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between cerebellar Purkinje cells and spatial working memory demonstrated in a lurcher/chimera mouse model system

Abstract: New emphasis has been placed upon cerebellar research because of recent reports demonstrating involvement of the cerebellum in non-motor cognitive behaviors. Included in the growing list of cognitive functions associated with cerebellar activation is working memory. In this study, we explore the potential role of the cerebellum in spatial working memory using a mouse model of Purkinje cell loss. Specifically, we make aggregation chimeras between heterozygous lurcher (Lc/+) mutant embryos and +/+ (wildtype) emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…These results confirm an association between cerebellum and linguistic abilities of individuals with DS and its potential role in their well-documented verbal deficits (Dulaney et al 1996;Laws and Bishop 2004;Vicari et al 2002). Moreover, according to both human and animal studies on short-term memory processing (Müller and Knight 2006;de Ribaupierre et al 2008) and, particularly, on spatial short-term memory abilities (Mandolesi et al 2001;Martin et al 2004) our data provide further evidence that the right posterior cerebellum have a role in spatial short-term memory abilities also in DS population.…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm an association between cerebellum and linguistic abilities of individuals with DS and its potential role in their well-documented verbal deficits (Dulaney et al 1996;Laws and Bishop 2004;Vicari et al 2002). Moreover, according to both human and animal studies on short-term memory processing (Müller and Knight 2006;de Ribaupierre et al 2008) and, particularly, on spatial short-term memory abilities (Mandolesi et al 2001;Martin et al 2004) our data provide further evidence that the right posterior cerebellum have a role in spatial short-term memory abilities also in DS population.…”
Section: Discussionsupporting
confidence: 90%
“…Since the two competencies are based on different memory functions acting on distinct time courses, the difference observed in HCbed rats could reflect a more limited storage capacity in working memory. This observation completely fits with the involvement of cerebellar circuits in the spatial working memory, already demonstrated in experimental [3,41,42] and clinical [43,44] studies.…”
Section: Exploration Of Cluster Configurationsupporting
confidence: 85%
“…Cerebellar Purkinje cell loss has been reported in both intraventricular 192 IgG-saporin infusion [14] and AD patients [44,45]. One study showed water maze acquisition delay by selective destruction of the cerebellar Purkinje cells [46], whereas others reported performance deficits by motor impairment in Purkinje cells lost in a mutant mouse model, indicative of a minor role for the cerebellum in spatial working memory [47]. In addition, others believe that activation of the cerebellum for working memory is involved in verbal working memory rather than spatial working memory [48].…”
Section: Discussionmentioning
confidence: 99%